Conception en didactique professionnelle d’une formation des tuteurs à l’activité d’observation des pratiques en éducation physique et sportive - Solange Ciavaldini-Cartaut (Recherches en Éducation)
This study concerns the observation of preservice teachers’ practice in Physical Education as preliminary stage in the mentoring post lesson conference during the year of their professionalization. Its exploratory aim is to show a professional didactics contribution (Orly & Vidal-Gomel, 2011; Pastré, 1999, 2005, 2011) for mentors’ training design based on the analysis of work. The relationship between the operational model and the abstract structure of the situation of observation allowed the creation of objects of training and highlight limits of the traditional mentor’s training. The results show the problems posed by the gap between the operational model and their style of mentoring (Clarke, 2006). Results allow estimating the potential apprenticeship of the observation of the preservice teacher’s practice as well as necessity to allow mentors to revisit their own faiths or designs of preservice teachers’ training for their professional development and skills.